2011
DOI: 10.1007/s10535-011-0175-7
|View full text |Cite
|
Sign up to set email alerts
|

Heat tolerance in rice mutants is associated with reduced accumulation of reactive oxygen species

Abstract: Four mutants induced by ethylmethane sulphonate (N22-H-dgl56, N22-H-dgl101, N22-H-dgl162 and N22-H-dgl219) with conspicuous dark green leaves were identified in the drought and heat-tolerant rice cultivar Nagina22 (N22), when screened under prolonged drought and heat conditions in field. During dark-induced senescence, these mutants maintained higher chlorophyll and carotenoid contents, and photochemical efficiency of photosystem 2 in comparison with N22. Following heat treatment, these mutants accumulated les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…However, the actual step of CK involvement in the Chl metabolic pathway and the mechanisms by which it could retard senescence are not known. An ethylmethane sulfonate (EMS)-induced, stay-green mutant ( N22-H-dgl162 ) of the Nagina22 (N22) rice cultivar showing delayed senescence was earlier identified in a field screen under prolonged drought and heat conditions ( Panigrahy et al , 2011 ). The aim of this study was to investigate the mechanism of CK-mediated delay of dark-induced senescence (DIS) in rice, taking cues from the stay-green mutant.…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual step of CK involvement in the Chl metabolic pathway and the mechanisms by which it could retard senescence are not known. An ethylmethane sulfonate (EMS)-induced, stay-green mutant ( N22-H-dgl162 ) of the Nagina22 (N22) rice cultivar showing delayed senescence was earlier identified in a field screen under prolonged drought and heat conditions ( Panigrahy et al , 2011 ). The aim of this study was to investigate the mechanism of CK-mediated delay of dark-induced senescence (DIS) in rice, taking cues from the stay-green mutant.…”
Section: Introductionmentioning
confidence: 99%
“…Nagina 22 is a well-known aus variety used routinely as a check for heat tolerance in rice (Jagadish et al, 2010). In a network project, EMS-induced stabilized N22 mutants were evaluated for different traits, such as tolerance to herbicide, heat, low P, water deficiency, and salinity and resistance to bacterial leaf blight and blast (Kulkarni et al, 2013(Kulkarni et al, , 2014Lima et al, 2015;Mithra et al, 2016;Mohapatra et al, 2014;Panigrahy et al, 2009Panigrahy et al, , 2011Panigrahy et al, , 2014Poli et al, 2013;Talla et al, 2016). As a part of the network project on functional genomics, a total of 2500 N22 mutants were screened at the Indian Institute of Rice Research (IIRR) under field conditions maintained with low P (Olsen P, <1.8) to identify low-P-tolerant and susceptible mutants.…”
mentioning
confidence: 99%
“…Marri et al 2005 also reported that RM250 was a marker interval of QTL for panicle length (pl2.1) in addition to spikelet number and grain weight in BC 2 testcross progeny of KMR3 introgression lines. Allele at locus RM274, associated with HSI of yield per plant was contributed by N22 and NH219, which were reported earlier as heat tolerant (Jagadish et al 2010b;Panigrahy et al 2011;Poli et al 2013). This marker was also linked to spikelet fertility in both control and heat stress conditions in RIL population of Zhongyouzao8 x Toyonishiki and the allele for heat tolerance was from the heat tolerant parent, Zhongyouzao8 (Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 73%